PENGARUH KEPEMIMPINAN ADAPTIF DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU MELALUI MOTIVASI BERPRESTASI GURU SD NEGERI SE KECAMATAN TUGU KOTA SEMARANG - Candro Herryka Putra; Tri Joko Raharjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher performance is a key determinant of educational quality and is influenced by both organizational and individual factors. Adaptive leadership and school culture are considered important organizational factors that can enhance teachers’ achievement motivation and ultimately improve their performance. This study aimed to examine the effects of adaptive leadership and school culture on teacher performance through teachers’ achievement motivation as a mediating variable among public elementary school teachers in Tugu District, Semarang City. A quantitative survey approach was employed involving 119 teachers selected as research respondents. Data were collected using questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The analysis included measurement model evaluation, structural model evaluation, and hypothesis testing through the bootstrapping procedure. The results revealed that adaptive leadership and school culture had positive and significant effects on teachers’ achievement motivation. Achievement motivation also had a positive and significant effect on teacher performance. However, adaptive leadership and school culture did not directly influence teacher performance. Achievement motivation partially mediated the relationship between adaptive leadership and teacher performance and fully mediated the relationship between school culture and teacher performance. These findings indicate that strengthening teachers’ internal achievement motivation is essential for translating adaptive leadership and a positive school culture into improved teacher performance. The study contributes to educational management by emphasizing the strategic role of achievement motivation in enhancing teacher performance.